Osteoporosis in Systemic Autoinflammatory Diseases: A Case-Control Study - Bindoli, Sara; Franceschet, Giulio; Galozzi, Paola; Zaninotto, Martina; Camozzi, Valentina; Sfriso, Paolo (Frontiers in Endocrinology, 2019)
Objective. To assess if patients affected by systemic autoinflammatory diseases (SAIDs) present an increased risk of osteoporosis (OP). Methods. 40 adults patients referred to the Rheumatology Unit of Padova University Hospital affected by Familial Mediterranean Fever (FMF), TNF-Receptor Associated Periodic Syndrome (TRAPS) and Mevalonate Kinase Deficiency (MKD) and 40 healthy subjects were enrolled. Blood and urine samples were collected in order to define phosphocalcic metabolism, including Receptor activator of nuclear factor kappa-Β ligand (RANKL) and osteoprotegerin (OPG), and among inflammatory markers serum amyloid A (SAA). Femur and lumbar dual-energy X-ray absorptiometry (DXA) scans were performed and Trabecular Bone Score (TBS) was calculated on DXA lumbar images. Results. We did not observe a statistically significant difference between Bone Mineral Density (BMD) and TBS of patients compared to controls. Also, the values of phosphocalcic metabolites in patients did not statistically differ from those in controls. However, SAA and OPG levels were significantly higher in patients compared to healthy subjects (p=0.0244 and p=0.0064, respectively). Conclusion. Patients of our cohort affected by FMF, TRAPS and MKD do not present an increased risk of OP compared to the healthy controls. TBS and BMD are similar between the two groups underlining a preserved bone quality in patients. High OPG levels could suggest a protective role and a bone re-balancing action in response to an inflammatory background. Finally, it should be taken into account a modulatory role played by a pro-inflammatory cytokine such as SAA on bone homeostasis.